Crystal structures of adenylylated and unadenylylated PII protein GlnK from Corynebacterium glutamicum - Grau, Florian; Burkovski, Andreas; Muller, Yves (Acta Crystallographica Section D : Structural Biology, 2021)
PII proteins are ubiquitous signaling proteins that are involved in the regulation of the nitrogen/carbon balance in bacteria, archaea, and some plants and algae. Signal transduction via PII proteins is modulated by effector molecules and post-Translational modifications in the PII T-loop. Whereas the binding of ADP, ATP and the concomitant binding of ATP and 2-oxoglutarate (2OG) engender two distinct conformations of the T-loop that either favor or disfavor the interaction with partner proteins, the structural consequences of post-Translational modifications such as phosphorylation, uridylylation and adenylylation are far less well understood. In the present study, crystal structures of the PII protein GlnK from Corynebacterium glutamicum have been determined, namely of adenylylated GlnK (adGlnK) and unmodified unadenylylated GlnK (unGlnK). AdGlnK has been proposed to act as an inducer of the transcription repressor AmtR, and the adenylylation of Tyr51 in GlnK has been proposed to be a prerequisite for this function. The structures of unGlnK and adGlnK allow the first atomic insights into the structural implications of the covalent attachment of an AMP moiety to the T-loop. The overall GlnK fold remains unaltered upon adenylylation, and T-loop adenylylation does not appear to interfere with the formation of the two major functionally important T-loop conformations, namely the extended T-loop in the canonical ADP-bound state and the compacted T-loop that is adopted upon the simultaneous binding of Mg-ATP and 2OG. Thus, the PII-Typical conformational switching mechanism appears to be preserved in GlnK from C. glutamicum, while at the same time the functional repertoire becomes expanded through the accommodation of a peculiar post-Translational modification.
CRIS-Team Scopus Importer:2021-03-19
Keywords: Adenylylation; Ampylation; Bacterial signal transduction; Crystal structures; Nitrogen starvation; Post-Translational modifications; T-loop conformations

Similarities in the structure of the transcriptional repressor AmtR in two different space groups suggest a model for the interaction with GlnK - Sevvana, Madhumati; Hasselt, Kristin; Grau, Florian; Burkovski, Andreas; Muller, Yves (Acta Crystallographica Section:F Structural Biology Communications, 2017)
Keywords: AmtR adenylylated GlnK complex stoichiometry; Corynebacterium glutamicum; Crystal-packing comparison; Nitrogen regulation; Transcription regulator effector complex

Structural insight into operator dre-sites recognition and effector binding in the GntR/HutC transcription regulator NagR - Fillenberg, Simon; Grau, Florian; Seidel, Gerald; Muller, Yves (Nucleic Acids Research, 2015)
The uptake and metabolism of N-acetylglucosamine (GlcNAc) in Bacillus subtilis is controlled by NagR (formerly named YvoA), a member of the widely-occurring GntR/HutC family of transcription regulators. Upon binding to specific DNA operator sites (dre-sites) NagR blocks the transcription of genes for GlcNAc utilization and interaction of NagR with effectors abrogates gene repression. Here we report crystal structures of NagR in complex with operator DNA and in complex with the putative effector molecules glucosamine-6-phosphate (GlcN-6-P) and N-acetylglucosamine-6-phosphate (GlcNAc-6-P). A comparison of the distinct conformational states suggests that effectors are able to displace the NagR-DNA-binding domains (NagR-DBDs) by almost 70 Å upon binding. In addition, a high-resolution crystal structure of isolated NagR-DBDs in complex with palindromic double-stranded DNA (dsDNA) discloses both the determinants for highly sequence-specific operator dre-site recognition and for the unspecific binding of NagR to dsDNA. Extensive biochemical binding studies investigating the affinities of full-length NagR and isolated NagR-DBDs for either random DNA, dre-site-derived palindromic or naturally occurring non-palindromic dre-site sequences suggest that proper NagR function relies on an effector-induced fine-tuning of the DNA-binding affinities of NagR and not on a complete abrogation of its DNA binding.

The complex formed between a synthetic RNA aptamer and the transcription repressor TetR is a structural and functional twin of the operator DNA-TetR regulator complex - Grau, Florian; Jaeger, Jeannine; Groher, Florian; Suess, Beatrix; Muller, Yves (Nucleic Acids Research, 2020)
RNAs play major roles in the regulation of gene expression. Hence, designer RNA molecules are increasingly explored as regulatory switches in synthetic biology. Among these, the TetR-binding RNA aptamer was selected by its ability to compete with operator DNA for binding to the bacterial repressor TetR. A fortuitous finding was that induction of TetR by tetracycline abolishes both RNA aptamer and operator DNA binding in TetR. This enabled numerous applications exploiting both the specificity of the RNA aptamer and the efficient gene repressor properties of TetR. Here, we present the crystal structure of the TetR-RNA aptamer complex at 2.7 Å resolution together with a comprehensive characterization of the TetR-RNA aptamer versus TetR-operator DNA interaction using site-directed mutagenesis, size exclusion chromatography, electrophoretic mobility shift assays and isothermal titration calorimetry. The fold of the RNA aptamer bears no resemblance to regular B-DNA, and neither does the thermodynamic characterization of the complex formation reaction. Nevertheless, the functional aptamer-binding epitope of TetR is fully contained within its DNA-binding epitope. In the RNA aptamer complex, TetR adopts the well-characterized DNA-binding-competent conformation of TetR, thus revealing how the synthetic TetR-binding aptamer strikes the chords of the bimodal allosteric behaviour of TetR to function as a synthetic regulator.
CRIS-Team Scopus Importer:2020-04-07